THE RELATIONSHIP BETWEEN DIABETES MELLITUS AND ORAL CAVITY DISEASES - Abduraxmonova, Shohista (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
This article explores the complex relationship between diabetes mellitus and oral cavity diseases from a medical and dental perspective. Diabetes mellitus is a chronic metabolic disorder characterized by high blood glucose levels due to insufficient insulin production or impaired insulin function. Prolonged hyperglycemia leads to systemic complications that also affect oral tissues. Studies have shown that patients with diabetes are more susceptible to periodontal diseases, dental caries, oral candidiasis, xerostomia (dry mouth), and delayed wound healing. Moreover, chronic oral infections can further complicate glycemic control, creating a bidirectional relationship between diabetes and oral diseases. This paper analyzes the underlying mechanisms, clinical manifestations, and preventive approaches aimed at maintaining oral health in diabetic individuals.